Analysis of emotional behavior disorders (anxiety) in children during covid 19 in east Lampung, Indonesia - Ismi Mu'alifah; Teguh Pribadi; Rahma Elliya (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: The COVID-19 virus or coronavirus disease is a virus that infects human respiration which was first discovered in Wuhan, China in 2019 and has spread throughout the world. Social distancing can cause acute stress and anxiety for children.Purpose: To analysis of emotional behavior disorders (anxiety) in children during covid 19 east Lampung, IndonesiaMethod: A quantitative, using a cross-sectional approach. The population is mothers who have children aged 5-11 years as respondents and can observe changes in their children's behavior during social restrictions because of the COVID-19 pandemic. The location is in Sumur Kucing village in 2021. A sample of 70 respondents was obtained using the snowball technique. Data collection techniques were carried out using a questionnaire. Statistical test analysis used is univariate and logistic regression.Results : The demographic data of respondents were mostly female 47 (67.1%), aged 7 years with an average (mean) of 7.41 years ± 1.853. Basic Education 46 (65.7%), doing routine sports at home (indoor) 53 (75.7%), having playing facilities 64 (91.4%). and the category is not anxious 66 (94.3%). Of all the most related variables, namely the availability of playing facilities at home on anxiety during COVID-19, with a p-value of 0.002.Conclusion: The statistical tests showed that anxiety in children during COVID-19 in Sumur Kucing Village in 2021, from several variables such as age, gender, education, and sports activities had no relationship with anxiety where the p-value was above 0.05. And the availability of play facilities at home is very important and is closely related to anxiety in children during the COVID-19 pandemic.